THE URGENCY OF ESTABLISHING A LOCAL GOVERNMENT REGULATION CONCERNING WASTEWATER MANAGEMENT IN LUWU REGENCY - Halide, Nirwana (Jurnal Al-Dustur, 2023)
Domestic wastewater is defined as wastewater contains various hazardous chemicals and microbes which causes environmental pollutions especially the source mainly for raw water sources as the drinking water from rivers and lakes, either the ground water. The importance in protecting and preserving environmental functions, thus obliged the regional government in Luwu Regency to manage the domestic wastewater. This study aims to understand the urgency of Establishing a Regional Regulation Concerning Wastewater Management in Luwu Regency. Through empirical juridical research conducted by the researcher to obtain research results i.e. The management of domestic wastewater in Luwu Regency is not yet optimal. Communities need adequate facilities and infrastructure e.g vacuum trucks and IPLT, education on domestic waste management to require the participations of the communities and private sectors can play an active role, and integrated funding and institutional needs. Luwu Regency needs the regulations in the form of Regional Regulations which is technically regulate the management of domestic wastewater in the particular importance for the community to have a better quality and healthy living environment to support the development of the good health and well-being of the communities.